Alleviation of nonlinear channel effects in long‐haul and high‐capacity optical transmission networks. (29th November 2021) - Ali, Farman; Habib, Usman; Muhammad, Fazal; Khan, Yousaf; Armghan, Ammar; Alenezi, Fayadh; Abbas, Ziaul Haq; Ali, Asar; Qamar, Muhammad Salman
Summary: Optical transmission networks (OTxNs) provide a cost‐effective solution towards ultrahigh data intercontinental transmission. However, nonlinear effects such as four‐wave mixing (FWM) and cross‐phase modulation (XPM) are the major performance limiting factors for OTxNs. This paper proposes the use of differential quadrature phase shift keying (DQPSK) modulation format and uneven channel spacings for dispersion compensation and investigates the nonlinear mitigation performance for a 32 channels ultradense wavelength division multiplexing (UDWDM) with data rate of up to 10 Gbps per channel. In addition, this paper presents an analysis on power budget and power penalties with a cost benefit analysis (CBA) for the proposed framework. The transmission link of the proposed UDWDM model is analyzed in terms of bit error rate (BER) for various lengths of optical fiber in long‐haul transmission, launch power, nonlinear effective area, and nonlinear refractive index. The analytical model is developed for mitigation of nonlinearity for the modeled UDWDM long‐haul and ultrahigh‐capacity system, beyond 1200‐km path span. The simulation results show systems advantages of having narrower spectrum than on‐off‐keying (OOK) modulation, significant tolerance to nonlinearities and low cost, compared with current OTxNs with 2.8‐dB optical signal‐to‐noise ratio (OSNR) improvement and successful mitigation of nonlinearities for as high launch powers as +4 dBm for such long distance transmission in dispersive channel. Abstract : We minimize the impact of nonlinear factors such as cross‐phase modulation (XPM) and four‐wave mixing (FWM) in the proposed system for the 1200 km of transmission length. Nonlinear impairments such as XPM and FWM are reduced by employing advance optical differential quadrature phase shift keying (DQPSK) modulation format, optimized launch power level, and erbium‐doped fiber amplifier and by adjusting linear and nonlinear dispersion parameters of the optical fiber. The limit of l × 10 − 3 has been used for bit error rate (BER) analysis for the proposed system, which is same as conventional Optical transmission networks (OTxNs). An optical signal‐to‐noise ratio (OSNR) improvement of 2.8 dB is observed for 1200 km of transmission distance. Moreover, mitigation of nonlinearities for high launch power as +4 dBm has been achieved which is conventionally limited to +2 dBm of launch powers for such long distances in a dispersive fiber.